Correlation between Lumbar Spine Facet Joint Orientation and Intervertebral Disk Degeneration: A Positional MRI Analysis - Jiang, Xin; Chen, Dong; Li, Zhongshi; Lou, Yahao (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Background and Study Aims The contribution of facet joint orientation (FO) to degeneration of the functional units of the lumbar spine remains unclear. The study used positional magnetic resonance imaging (MRI) to evaluate the association between intervertebral disk degeneration and FO at the L3–L4 to L5–S1 spinal segments.Material and Methods This was a retrospective study of 450 outpatients admitted to the Spine Surgery Department of our hospital between January 2013 and January 2015 and with positional lumbar MRI data. Grade of intervertebral disk degeneration, FO relative to the midsagittal plane, vertebral translation (VT), and angular variation (AV) were assessed.Results No effect of baseline characteristics (age, sex, and body mass index) on intervertebral disk degeneration was observed. A significant difference in VT and AV was only present between grades 1 + 2 versus 4 at L5–S1 (both p = 0.005), and in FO only at L5–S1 between grades 1 + 2 versus 4 (p = 0.03) and grades 3 versus 4 (p = 0.04). AV and VT were correlated at all three lumbar segments (r = 0.224–0.309; p ≥ 0.01), with a correlation between FO and AV only at L3–L4 (r = 0.141; p = 0.035).Conclusion Disk degeneration was associated with FO only at L5–S1. AV and VT of spinal segments of the mid to lower lumbar spine did not correlate with FO.
Keywords: Lumbar Spine; facet orientation; flexion-extension movement; degeneration; magnetic resonance imaging